2008
DOI: 10.4067/s0717-95022008000100015
|View full text |Cite
|
Sign up to set email alerts
|

Ortopantomographic Blind Test of Mandibular Ramus Flexure as a Morphological Indicator of Sex in Chilean Young Adults

Abstract: SUMMARY: Loth & Henneberg (1996) described a simple morphological feature for sex determination by observing the flexure of the posterior margin of the mandibular ramus, at the level of the plane occlusal. The purpose of this study is to analyze the level of agreement for determining the sex by observing the parameters described by Loth and Henneberg, in ortopantomography of totally dentate Chilean young adults. This study is based on 188 files of ortopantomography acquired from the Department of Radiology of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 17 publications
0
2
1
Order By: Relevance
“…In the present study, the technique proved accurate for correctly identifying males than females. Moreover, the results were better than for other research in adults, which identified the prediction accuracy of 48.3% for males (Suazo Galdames et al, 2008). Although we found a discrete accuracy of FA in sexual dimorphism, this minimally-invasive technique is suitable for forensic investigations when associated with other methods to improve results in sex estimation.…”
Section: Discussioncontrasting
confidence: 59%
“…In the present study, the technique proved accurate for correctly identifying males than females. Moreover, the results were better than for other research in adults, which identified the prediction accuracy of 48.3% for males (Suazo Galdames et al, 2008). Although we found a discrete accuracy of FA in sexual dimorphism, this minimally-invasive technique is suitable for forensic investigations when associated with other methods to improve results in sex estimation.…”
Section: Discussioncontrasting
confidence: 59%
“…In our study the parameter ramus, flexure was not included as this parameter did not give any conclusive evidence ofsexual dimorphism in the past studies reported by Shiva Prakash, Aparna et al ., and Galdames. [ 11 12 13 14 ]…”
Section: Discussionmentioning
confidence: 99%
“…A synopsis of various radiographic studies on mandible in sex dimorphism was presented in Table 1. [45678910111213141516171819] And synopsis of skeletal parameters of morphometric studies on dry mandible in sex dimorphism was presented in Table 2. [12202122232425262728293031323334353637]…”
Section: Introductionmentioning
confidence: 99%